2011
DOI: 10.21608/jppp.2011.86427
|View full text |Cite
|
Sign up to set email alerts
|

TOXICITY OF HONEYBEE PROPOLIS AGAINST Pectinophora gossypiella (SAUND.), Spodoptera littoralis (BOISD.) AND Aphis craccivora (KOCH)

Abstract: Propolis is a natural resin produced by honeybees colonies in two kinds (Egyptian and Chinese propolis) were tested against some injurious pests i.e. eggs, newly hatched and 4 th instars larvae of the pink bollworm, Pectinophora. gossypiella (Saund.), 4 th instars larvae of the cotton leafworm, Spodoptera. littoralis (Boisd.) and the cowpea aphid, Aphis craccivora (Koch) adults and nymphs. The results showed that; the newly hatched larvae is considered the most susceptible stage of the pink bollworm, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In addition, Leon-Reyes, et al (2010) reported that Jasmonates (JAs) and salicylic acid (SA) are plant hormones that play pivotal roles in the regulation of induced defenses against microbial pathogens of necrotrophic fungus, Alternaria brassicicola and insect herbivores, Pieris rapae. Meanwhile, Amer and Nafea (2011) found that propolis is a natural resin produced by honeybees colonies in two kind (Egyptian and Chinese propolis) were tested against some injurious pests i.e. eggs, newly hatched and 4 th instars larvae of the pink bollworm, Pectinophora.…”
Section: Asa: Acetyl Salicylic Acid Cpm: Chlorpheniramine Maleatementioning
confidence: 99%
“…In addition, Leon-Reyes, et al (2010) reported that Jasmonates (JAs) and salicylic acid (SA) are plant hormones that play pivotal roles in the regulation of induced defenses against microbial pathogens of necrotrophic fungus, Alternaria brassicicola and insect herbivores, Pieris rapae. Meanwhile, Amer and Nafea (2011) found that propolis is a natural resin produced by honeybees colonies in two kind (Egyptian and Chinese propolis) were tested against some injurious pests i.e. eggs, newly hatched and 4 th instars larvae of the pink bollworm, Pectinophora.…”
Section: Asa: Acetyl Salicylic Acid Cpm: Chlorpheniramine Maleatementioning
confidence: 99%